Georges de Scudéry et le théâtre - Steigerwald, Jörn (Papers on French Seventeenth Century Literature XLVI, 91)

Assessing dimensions of inclusion from students’ perspective – measurement invariance across students with learning disabilities in different educational settings - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin; Schwab, Susanne; Gebhardt, Markus (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

'Runzelsex' im Kino. Die Sexualisierung alter Körper in Andreas Dresens Wolke 9 zwischen Provokation und Subversion - Süwolto, Leonie (Figuren des Provokativen und Subversiven. Körper und Sexualität multimedial)

La novelística italiana y la comedia de Lope de Vega - Schlieper, Hendrik (Los pre-textos del teatro áureo español. Condicionantes literarios y culturales. (Biblioteca Áurea Hispánica, 128))

,Le Romain‘ selon Scudéry – La Mort de César - Schlieper, Hendrik (Papers on French Seventeenth Century Literature, 91)

Geschichtsbetrachtung jenseits der Norm: Städte- und Reisefeuilletons von Franz Hessel, Joseph Roth und Siegfried Kracauer als politische Reflexionsräume und kleine Bildarchive historischen Wissens - Öhlschläger, Claudia (Konformieren. Festschrift für Michael Niehaus)

Lemma „Wild/Wildnis" - Öhlschläger, Claudia (Neue Romantik. Eine kleine Literaturgeschichte 1989-2019)

Introduction: une apologie de Georges de Scudéry et de son théâtre - Steigerwald, Jörn (Georges de Scudéry et le théâtre. Papers on French Seventeenth Cenrury Literature XLVI, 91)

Un combat d'amour en pastoral: la tragi-comédie "Ligdamen et Lidias ou La ressemblance“ - Steigerwald, Jörn (Georges de Scudéry et le théâtre. Papers on French Seventeenth Cenrury Literature XLVI, 91)

Sinnliche Machtspiele: Die Erotik des Scrabblespiels in Margaret Atwoods Roman und Bruce Millers Serienadaption von "The Handmaid's Tale" - Hannebohm, Ronja (Erotik in Literatur und Theater)

Operatoren „to go“. Ein Arbeitsheft zum Nachschlagen und Üben für das Fach Deutsch

Feilke revisited. 60 Stellenbesuche

Schreiben zu Texten. Fördermagazin Sekundarstufe Deutsch 4/2019

Operatoren „to go“. Praxis Deutsch 274

Was ist zu tun? Operatorenformulierungen - Rezat, Sara; Feilke, Helmuth (Operatoren „to go“. Ein Arbeitsheft zum Nachschlagen und Üben für das Fach Deutsch)

Sprache und Sprachgebrauch untersuchen und reflektieren - Rezat, Sara (Fachdidaktik Deutsch. 3., überarbeitete und aktualisierte Auflage.)

Fachspezifische Leistungsbewertung und –beurteilung - Rezat, Sara (Fachdidaktik Deutsch. 3., überarbeitete und aktualisierte Auflage)

Schreiben zu Texten. Potenziale eines vielgestaltigen Aufgabensettings für das Lesen und Schreiben nutzen - Rezat, Sara; Schüler, Lisa (Fördermagazin Sekundarstufe Deutsch 4/2019)

Filme im Podcast unter die Lupe nehmen - Rezat, Sara; Schüler, Lisa (Fördermagazin Sekundarstufe Deutsch 4/2019, (+Downloadmaterial))

Textdidaktische Gattungen: Etüden im Schreibunterricht? - Rezat, Sara (Feilke revisited. 60 Stellenbesuche)

Operatoren „to go”. Prozedurenorientierter Schreibunterricht. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 274)

CLIL(iG) im Literaturunterricht der Sekundarstufe I? Konzepte der Fremdsprachendidaktik in einem integrativen Deutschunterricht am Beispiel von Emine Sevgi Özdamars „Karagöz in Alamania. Schwarzauge in Deutschland“ - Zierau, Cornelia; Kofer, Martina (Jahrbuch Deutsch als Fremdsprache 2016)

Stifterverband für die Deutsche Wissenschaft e.V.: Lehrkräftebildung für die Schule der Vielfalt. Eine Handreichung des Netzwerks Stark durch Diversität. (Mitautorin) - Zierau, Cornelia

Türkisch-deutsche Studien Jahrbuch 2018: Übersetzung als Kulturaustausch

Die Wissenschaftler und das verantwortliche Handeln im schweizerischen Drama. Friedrich Dürrenmatts Physiker Möbius und Lukas Bärfuss' Mediziner Gustav Strom - Famula, Marta (Vom Gipfel der Alpen... Das schweizerische Drama und Theater im 20. und 21. Jahrhundert)

„…ein gewisses Verhältnis zum Leben“. Die lebensweltliche Bedeutung der Schinkensemmel im Erzählwerk Thomas Manns - Famula, Marta (Dinge im Werk Thomas Manns (= inter/media 11))

Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, M.; Frey, P.; Kleffel, T.; Drummer, D.; Merklein, M. (AIP Conference Proceedings)

Vollvalidiertes thermisches Netzwerk eines RWDR- Ersatzsystems - Burkhart, C; Heimes, J; Weyrich, D; Magyar, Balázs; Sauer, B

Downturns are a better time for deal hunting - Kengelbach, Jens; Keienburg, Georg; Gell, Jeff; Nielsen, Jesper; Bader, Maximilian; Degen, Dominik; Sievers, Sönke (The 2019 M&A-Report)

Determinants of Financial Misreporting: A Survey of the Financial Restatement Literature - Sievers, Sönke; Sofilkanitsch, Christian

Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Sonderpädagogik als Erfahrungs- und Praxiswissenschaft. Geistes-, sozial- und kulturwissenschaftliche Perspektive - Dederich, M; Ellinger, S.; Laubenstein, Désirée

Beurteilung der Leistungsfähigkeit von Schmierstoffen mittels eines FZG Prüfstandes - Keßler, A; Elkenkamp, P; Magyar, Balázs; Mayer, C (Tribologie und Schmierungstechnik)

Teamentwicklung und Teamkooperation - Guthöhrlein, K.; Laubenstein, Désirée; Lindmeier, C.

Reibenergie basierte Verschleißsimulation für Radialwellendichtringe - Foko Foko, F; Sauer, B; Magyar, Balázs

The ‘Learning Office’ as an Approach for Inclusive Education in Mathematics: Opportunities and Challenges - Laubenstein, Désirée; Guthöhrlein, Kirsten; Lindmeier, Christian; Scheer, David; Sponholz, Dirk (In: Kollosche, D.; Marcone, R.; Knigge, M.; Godoy Penteado, M.; Skovsmose, O. (Hrsg.). Inclusive Mathematics Education. State-of-the-Art Research from Brazil and Germany)

Das Praxissemester von angehenden Lehrkräften - Caruso, Carina

Praxissemester (Religion) in NRW: Bilanz und Perspektiven - Caruso, Carina; Woppowa, Jan
Since the winter semester 2014 / 2015 long-term internships have become an integral part of the second master semester at universities in North Rhine-Westphalia. One aim is to improve the development of competencies of prospective teachers. This anthology provides an insight into perspectives of long-term internships in North Rhine-Westphalia referring especially to internships of those prospective teachers, who are going to be teachers for religious education. First Bardo Herzig and Christoph Wiethoff present the plan, the structure and the content of long-term internship at Paderborn University. They take pedagogy as their example. Petra Herzmann and Anke B. Liegmann provide a comprehensive survey of qualitative research on long-term internships and present ideas of a qualitative research programme. Carina Caruso and Andreas Seifert focus on the development of pedagogical knowledge of prospective teachers of religious education during the practice phase. Malte Kling gives a summary of his thesis referring to the change of roles of prospective teachers of religious education. Guido Hunze und Gudrun Lohkemper have a look at the relation between theory and practice for a successful professionalization. Norbert Brieden and Monika Tautz compare the accompaniment of students at Cologne and Wuppertal University and put forward an impetus for teaching at university. Mirjam Zimmermann looks at spirituality in internships. Guido Meyer and Carsten Misera give a definition of heterogeneity as a starting point of the development of the teacher habitus. Christoph Vogelsang and Ulrich Feeser-Lichterfeld contribute to a further combination of perspectives on internships. Carina Caruso and Jan Woppowa give a final summary looking especially at future tasks of the design of long-term internships in theology.

On the nomological net of (non-) workaholic subtypes - Ontrup, Greta; Patrzek, Justine (Career Development International)

Estimation of Nematic Order Parameters via Haller Analysis of 1H NMR Spectra of Liquid Crystals - Tang, Ming-xue; Schmidt, Claudia (Chinese Journal of Magnetic Resonance)
The Haller relationship was applied to estimate the nematic order parameter S from 1H NMR spectra of fully protonated liquid crystals aligned in the magnetic field. The NMR line shapes were approximated as doublets of very broad peaks. Both the temperature-dependent doublet Splitting and the full width at half maximum of the whole spectra were used for Haller extrapolation. The order parameters obtained with the proposed approach for 4-cyano-4'-pentylbiphenyl (5CB) and the nematic mixture E7 were found to be in good agreement with previously reports.
Keywords: nematic liquid crystal; order parameter; Haller analysis; 1H NMR

Speech Processing for Digital Home Assistance: Combining Signal Processing With Deep-Learning Techniques - Haeb-Umbach, Reinhold; Watanabe, Shinji; Nakatani, Tomohiro; Bacchiani, Michiel; Hoffmeister, Bjoern; Seltzer, Michael L.; Zen, Heiga; Souden, Mehrez (IEEE Signal Processing Magazine)
Once a popular theme of futuristic science fiction or far-fetched technology forecasts, digital home assistants with a spoken language interface have become a ubiquitous commodity today. This success has been made possible by major advancements in signal processing and machine learning for so-called far-field speech recognition, where the commands are spoken at a distance from the sound capturing device. The challenges encountered are quite unique and different from many other use cases of automatic speech recognition. The purpose of this tutorial article is to describe, in a way amenable to the non-specialist, the key speech processing algorithms that enable reliable fully hands-free speech interaction with digital home assistants. These technologies include multi-channel acoustic echo cancellation, microphone array processing and dereverberation techniques for signal enhancement, reliable wake-up word and end-of-interaction detection, high-quality speech synthesis, as well as sophisticated statistical models for speech and language, learned from large amounts of heterogeneous training data. In all these fields, deep learning has occupied a critical role.

„Die Schulbänke standen hintereinander“. Darstellendes Schreiben über die Schule früher - Tophinke, Doris (Praxis Deutsch)

Konstruktionale Aspekte schriftkultureller Autozentrierung im Spätmittelalter. Zu einer markanten Neuerung in der Buchführung der Hansekaufleute des 14. Jahrhunderts - Tophinke, Doris (Linguistische Kulturanalyse)

Muster - Tophinke, Doris (Feilke revisited. 60 Stellenbesuche)

Dialekte heute (Basisartikel) - Tophinke, Doris (Paxis Deutsch)

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Encrypted Model Predictive Control in the Cloud - Schulze Darup, Moritz (Privacy in Dynamical Systems)

Towards real-time ADMM for linear MPC - Schulze Darup, Moritz; Book, Gerrit; Giselsson, Pontus (2019 18th European Control Conference (ECC))